절연유에서 부분방전에 의한 극초단파 신호 특성분석 - 朱炯俊(Hyoung-Jun Ju); 具嬋根(Sun-Geun Goo); 朴基濬(Ki-Jun Park); 韓基善(Ki-Seun Han); 尹珍烈(Jin-Yul Yoon) (전기학회 논문지 P권, 57(1), 2008)
We have designed 4 types(void in insulation paper, protrusion electrode, floating electrode, surface discharge) of partial discharge(PD) defect to simulate typical faults found in oil filled power transformers. Ultra-high frequency(UHF) radiation due to PD was measured using a UHF measuring system and a conventional PD measuring system, simultaneously. Electromagnetic radiation spectra of these defects show UHF radiation up to about 1.5-2 GHz range. The phase resolved partial discharge(PRPD) patterns of UHF radiation from the PD defects were also measured and the pattern reveals distinct feature for each defect types. The UHF measuring could be used to detect PDs in oil filled transformers and analysis of the PRPD pattern should provide useful information on origin of PD signal.